The Influence of KPI (Key Performance Indicator), Workload and Career Development on Employee Performance at PT Pegadaian Pringgan Medan - Tampubolon, Nikita Stefani; Putriani, Hafiza; Sipahutar, Sri Putri Isabela; Rostina, Cut Fitri; Fauzi, Fauzi (Lembaga Riset Ilmiah, 2025)
The purpose of this research is to examine the influence of Key Performance Indicators (KPIs), workload, and career development on employee performance at PT. Pegadaian Pringgan Medan. The background of this research is based on the condition of employee performance that is not optimal and there are problems related to the implementation of KPIs, increased workload, and career development systems that are considered less than optimal. The research method used is a quantitative approach. The population in this research is around 40 employees and all of them are sampled through the saturated sampling technique. The data analysis technique used multiple linear regression with the help of the SPSS program. The results of the study explained that partially, KPIs and career development have a positive and significant effect on employee performance, while workload has no effect and is insignificant. Simultaneously, these three variables have a positive and significant effect on employee performance with a contribution of 88.1%. These findings indicate that the implementation of measurable KPIs and effective career development is critical in improving employee performance.